Implementation and Research of Classroom Action Research (CAR) to Enhance Teacher Competence: Pelatihan dan Implementasi Penelitian Tindakan Kelas (PTK) Untuk Meningkatkan Kompetensi Guru - Reny, Reny; Ningsih, Purnama; Said, Irwan; Hamzah, Baharuddin; Aminah, Sitti; Pulukadang, Sri Hastuti Virgianti (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
Low understanding among teachers regarding the concepts and benefits of Classroom Action Research (CAR) as a means of professional development is one of the main problems at SD Negeri 2 Labuan. Most teachers are not yet accustomed to systematically reflecting on their teaching practices thru classroom-based research. This resulted in very limited teacher participation in CAR activities, and the learning innovations that were supposed to emerge from this process were also hindered. To address this, the Faculty of Education and Teacher Training at Tadulako University conducted a Community Service (PkM) activity to improve teacher competence thru training and the implementation of Classroom Action Research. This activity included training, mentoring in preparing CAR as well as reflection and evaluation. The evaluation results show an 84% increase in teachers' understanding of CAR. Full support from the school and active participation from the teachers also contributed positively to the success of this activity.